Clarifying Misconceptions Understanding Hand-Cutting Punishments in the Al-Sariqah Crime Context - Haq, Islamul (Sharia and Law Faculty, 2024)
This research aims to explore understanding and clarify potential misconceptions related to hand-cutting punishment in the context of Al-Sariqah crime (theft) within Islamic law. The research also encompasses an examination of legal approaches and justice in the implementation of this punishment. By analyzing various literary sources, particularly the opinions of scholars and Islamic legal literature, this study highlights the stringent standards and conditions that must be met for hand-cutting punishment to be applied. This research will utilize academic databases, digital libraries, and other reliable sources to gather scholarly articles, books, and conference papers discussing aspects of hand amputation punishment in the context of al-Sariqah. the research dispels the common belief that it can be haphazardly applied. The stringent prerequisites, including evidence, legal clarity, and understanding the perpetrator's circumstances, underline that hand amputation is not an arbitrary measure but is reserved for specific circumstances.